Starvation Heights - Olsen, Gregg (Three Rivers Press, 2005)
"In 1911 two wealthy British heiresses, Claire and Dora Williamson, came to a sanitorium in the forests of the Pacific Northwest to undergo the revolutionary "fasting treatment" of Dr. Linda Burfield Hazzard. It was supposed to be a holiday for the two sisters. But within a month of arriving at what the locals called Starvation Heights, the women were emaciated shadows of their former selves, waiting for death. They were not the first victims of Linda Hazzard, a quack doctor of extraordinary evil and greed who would stop an nothing short of murder to achieve her ambitions. As their jewelry disappeared and forged bank drafts began transferring their wealth to Hazzard's accounts, Dora Williamson sent a last desperate plea to a friend in Australia, begging her to save them from the brutal treatments and lonely isolation of Starvation Heights... one of the most unusual and disturbing criminal cases in American history." -- back cover.